2017
DOI: 10.15302/j-fase-2016116
|View full text |Cite
|
Sign up to set email alerts
|

Critical roles of chemokines and cytokines in antiviral innate immune responses during rabies virus infection

Abstract: The innate immune response is the first line of defense against viral invasion and pro-inflammatory chemokines and cytokines have a critical function in the innate immune responses against virus infections. The ability of a rabies virus (RABV) to induce the expression of chemokines and cytokines can lead to viral clearance from the central nervous system (CNS), whereas the ability to evade such expression and activation contributes to virulence and pathogenicity. In this review, the crucial contribution of che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…We also noticed that 6(OH)Mel can enhance the C-X-C motif chemokine ligand 1 (CXCL1) level ( Figure 4 D). CXCL1 is an antimicrobial protein, which also plays a role in the antiviral innate immune response [ 62 ]. These findings are consistent with the above bioinformatic analyses and well-documented immunomodulatory and protective properties of melatonin [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…We also noticed that 6(OH)Mel can enhance the C-X-C motif chemokine ligand 1 (CXCL1) level ( Figure 4 D). CXCL1 is an antimicrobial protein, which also plays a role in the antiviral innate immune response [ 62 ]. These findings are consistent with the above bioinformatic analyses and well-documented immunomodulatory and protective properties of melatonin [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Rabies virus (RABV) genomes contain five genes, each of which encodes multi-functional proteins with the ability to affect the host immune response in some way to aid the replication and spread of the virus [ 18 ]. The importance of these immune-suppressive effects is evident when comparing laboratory-attenuated strains to wild-type RABVs, as the former lack many of these immune-suppressive capabilities, enabling the virus to be cleared from the central nervous system (CNS) by the host’s immune response [ 19 ]. Furthermore, studies have demonstrated that it is feasible to clear wild-type RABV infection from the CNS when the host immune response remains unimpeded [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cytokines are mainly proteins or peptides generally associated with inflammation and cell differentiation, including interleukins (IL), interferons (IFNs), etc. They can contribute to the diagnosis and treatment of diseases [ 1 , 2 ], for example, they are conducive to the treatment of hematopoietic dysfunction [ 3 ], tumor [ 4 ], infection [ 5 , 6 ] and inflammation [ 7 , 8 ]. With the post-genomic era coming, the quantity of new proteins has increased dramatically.…”
Section: Introductionmentioning
confidence: 99%